Influence of Occlusal Force on Electroencephalograms in Edentulous Patients. Issue 7 (15th January 2015) - Morokuma, Masakazu; Yoneyama, Yoshikazu; Matsuda, Risa; Hosoi, Toshio; Ohkubo, Chikahiro
Abstract Purpose This study explored the effect of improved occlusal force resulting from complete denture treatment on electroencephalogram (EEG) findings to determine if such an outcome is a factor contributing to activation of synaptic/neuronal dysfunction in the brain. Materials and Methods Twenty‐three individuals with complete upper and lower dentures who visited the Department of Removable Prosthodontics at Tsurumi University Dental Hospital were included in this study. The Dental Prescale Occluzer FPD‐705 system was used to perform an objective measurement of occlusal force before and after denture treatment. EEGs were recorded for 3 minutes in patients receiving complete dentures before and after denture treatment. Then, Dα values were calculated using a diagnosis method of neuronal dysfunction analysis to evaluate changes in synaptic/neuronal dysfunction of the brain. To investigate whether occlusal force affects Dα, Spearman's rank correlation coefficient (α = 0.05) was used to test the association between occlusal force (N) and Dα based on the rates of change in occlusal force and Dα calculated by dividing the measurement values after denture treatment by the measurement values before denture treatment. Results Medial occlusal force increased from 184.9 N before treatment to 277.2 N after treatment. A statistically significant increase in occlusal force (p < 0.05) was observed, with a total of 22 participants exhibiting increased occlusal force after denture treatment. The medial Dα value increased from 0.943 before treatment to 0.957 after treatment. A statistically significant increase in Dα (p < 0.05) was observed, and a total of 19 participants exhibited increased Dα values after denture treatment. The regression line was calculated as Y = 14.049X – 12.450. As occlusal force increased, Dα values increased as well. A significant positive correlation was observed between occlusal force and Dα (r = 0.498, p < 0.05). Conclusions A positive correlation was observed between improved occlusal force attained via complete denture treatment and the activation of Dα. This finding reveals occlusal force as a denture treatment outcome that contributes to the activation of synaptic/neuronal dysfunction in the brain.